Classroom Detracking in the US Examples for School Leadership - Thornton, Margaret (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book offers a comprehensive examination of how school leaders can institute detracking in their school with research-based best practices. Since the 1980s, researchers and educators have called for detracking as an alternative to the common practice of seperating students into classes by supposed achievement levels. In its most basic form, detracking places students in the same classroom regardless of perceived previous achievement. In this book, Thornton focuses on four high-quality detracking programs across the US to provide a roadmap of best practices for school leaders. Focusing on schools in diverse suburban and urban areas, this book will be beneficial to a wide variety of school leaders as well as school leadership researchers. With the effects of the pandemic still felt in schools and the heated debates at school boards across the country, leaders and researchers both need a path forward for equity-focused work. This book helps to provide way finders on that path while also speaking to the need to travel the path in the first place. Margaret Thornton is Assistant Professor at Rowan University, USA. She studies equity-focused school leadership development, school leadership for detracking, and Critical Race Theory. .
1."What kid likes to read?!": Understanding How and Why Students Are Sorte -- 2 "Hey, let's challenge yourselves": Beginning Detracking at Eastern High School -- 3 "The kids can handle it": Moving to an Honors-for-Most Model at Queen Anne High School -- 4 Dismantling a "school-within-a-school": At Sunnydale High School -- 5 "We're not done": Building an IB Program for (Nearly) All at Johnson High School -- 6 Conclusion.
Keywords: Schools; Social justice; Education and state; Psychology, Industrial; Leadership; Educational tests and measurements; Education -- Curricula; School and Schooling; Social Justice; Educational Policy and Politics; Leadership Psychology; Assessment and Testing; Curriculum Studies